Enhanced insulation resistance and electrical properties of BiFe1-x(Zn0.5Ti0.5)xO3-BaTiO3 lead-free piezoceramics. Issue 7 (May 2018) - Chen, Jian-Yin; Zhang, Bo-Ping; Zhu, Li-Feng; Cheng, Shuai; Tang, Yu-Cheng
Abstract: The phase structure, microstructure and electrical properties of 0.7BiFe1- x (Zn0.5 Ti0.5 ) x O3 –0.3BaTiO3 (0.00 ≤  x  ≤ 0.07) (BFZT x -BT) ceramics prepared via a conventional solid-state reaction method were studied by emphasizing the effect of Bi(Zn0.5 Ti0.5 )O3 . BFZT x -BT ceramics show coexisting rhombohedral-pseudocubic ( R - PC ) phase when 0.00 ≤  x  ≤ 0.05 and a single PC structure at x =  0.07. The fraction of R to PC phase ( C R / C PC ) calculated by Rietveld refinement was 53/47, 51/49, 21/79, 14/86 at x  = 0.00, 0.01, 0.03 and 0.05, respectively. Adding (Zn0.5 Ti0.5 ) 3+ leads to an enhanced insulation resistance 130 GΩ·cm for x  = 0.05 composition under 1 kV/mm, which is one order of magnitude higher than that at 0.00 ≤  x  ≤ 0.03. Owing to the synergy effects of polarization performance and proper C R / C PC fraction, optimum electrical properties of BFZT x -BT ceramics d 33 = 135 pC/N, T c = 482 °C, k p = 25% were attained at x  = 0.05. Our result indicates that the formation of ternary solid solution is an effective and convenient strategy to enhance the electrical performance of BF-BT based piezoceramics by tailoring insulation resistance along with the phase structure.